The effectiveness of topical pilocarpine in carboxymethylecllulose saliva substitute for post irradiation xerostomia in patients with head and neck carcinoma compared with carboxymethylcellulose solution alone : a randomized-controlled trial - Pariyanan Jaruchinda (Chulalongkorn University, 2014)
Thesis (M.Sc.)--Chulalongkorn University, 2007